MTOR inhibitors effects on regulatory T cells and on dendritic cells. Issue 1 (December 2016) - Stallone, Giovanni; Infante, Barbara; Lorenzo, Adelaide; Rascio, Federica; Zaza, Gianluigi; Grandaliano, Giuseppe
Abstract The mammalian target of rapamycin (mTOR), a cytoplasmic serine/threonine kinase, represents a key biologic "switch" modulating cell metabolisms in response to environmental signals and is now recognized as a central regulator of the immune system. There is an increasing body of evidence supporting the hypothesis that mTOR inhibitors exhibit several biological properties in addition to immunosuppression, including anti-neoplastic effects, cardio-protective activities, and an array of immunomodulatory actions facilitating the development of an operational graft tolerance. The biological mechanisms explaining how mTOR inhibition can enable a tolerogenic state are still largely unclear. The induction of transplant tolerance might at the same time decrease rejection rate and minimize immunosuppression-related side effects, leading to an improvement in long-term graft outcome. In this scenario, T cell immunoregulation has been defined as the hallmark of peripheral tolerance. Two main immunologic cell populations have been reported to play a central role in this setting: regulatory T cells (Tregs) and dendritic cells (DCs). In this review we focus on mTOR inhibitors effects onTreg and DCs differentiation, activation, and function in the transplantation setting.